harges over Book Debts: Implications of Spectrum Plus - Teh, Wei Wei (Journal of Malaysian and Comparative Law, 2006)
In my opinion, the essential characteristic of a floating charge, the characteristic that distinguishes it from a fixed charge, is that the asset subject to the charge is not finally appropriated as a security for the payment of the debt until the occurence of some future event. In the meantime the chargor is left free to use the charged asset and to remove it from the security ... Moreover, recognition that this is the essential characteristic of a floating charge reflects the mischief that the statutory intervention to which I have referred to was intended to meet and should ensure that preferential creditors continue to enjoy the priority that s 175 of the [Insolvency] Act and its statutory predecessors intended them to have.